Improving Hijrah Methods in Finding Happiness Life - Salma Rozana; Munisa Munisa; Rita Nofianti; Rika Widya (Budapest International Research and Critics University, 2021)
This research is a study of the concept of happiness in emigration according to the view of the Sahabat Hijrahkuu Medan community. The phenomenon of hijrah is not something new. Still, the problem is that many hijrah actors are inconsistent and not committed to hijrah. The reason for this is the mistake of thinking that hijrah is something that is restraining, thus causing unhappiness. This research is expected to increase knowledge about the importance of emigrating and feeling happy in emigrating, understanding the meaning of happiness from an Islamic perspective. This study will also describe the various activities carried out by the Sahabat Hijrahkuu community in Medan. From the results of data analysis, researchers found that the efforts of the Sahabat Hijrahkuu Medan community were very high at 40%, and the lowest level was 5% of the total. The congregation's response to the presence of this community was quite positive, namely 40%, and the lowest level was 5% of the total. As for this study, the researcher would like to give some advice to the Sahabat Hijrahkuu community in Medan to strengthen the emigration movement with more efficient collaboration with other communities or organizations.